Construction of the 2024 Presidential Candidate Campaign on the Mata Najwa YouTube Channel - Basarah, Finy Fitrya (Universitas Mercu Buana, 2024)
The General Election ended on February 14, 2024, the Indonesian public is waiting for an official announcement from the General Election Commission (Komisi Pemilihan Umum). Previously, during the campaign period, after the campaign and waiting for the decision, news about the election, especially the Presidential Campaign, was widely discussed in the media, including YouTube.Najwa Shihab's YouTube channel, broadcast “Jejak Kampanye Capres 2024” (Traces of the 2024 Presidential Candidate Campaign) before the election was held. The content is divided into